Solve for k -(k+12)=6(-12)

Math
-(k+12)=6(-12)
Multiply each term in -(k+12)=6(-12) by -1
Tap for more steps…
Multiply each term in -(k+12)=6(-12) by -1.
-(k+12)⋅-1=6(-12)⋅-1
Simplify -(k+12)⋅-1.
Tap for more steps…
Apply the distributive property.
(-k-1⋅12)⋅-1=6(-12)⋅-1
Multiply -1 by 12.
(-k-12)⋅-1=6(-12)⋅-1
Apply the distributive property.
-k⋅-1-12⋅-1=6(-12)⋅-1
Multiply -k⋅-1.
Tap for more steps…
Multiply -1 by -1.
1k-12⋅-1=6(-12)⋅-1
Multiply k by 1.
k-12⋅-1=6(-12)⋅-1
k-12⋅-1=6(-12)⋅-1
Multiply -12 by -1.
k+12=6(-12)⋅-1
k+12=6(-12)⋅-1
Simplify 6(-12)⋅-1.
Tap for more steps…
Multiply 6 by -12.
k+12=-72⋅-1
Multiply -72 by -1.
k+12=72
k+12=72
k+12=72
Move all terms not containing k to the right side of the equation.
Tap for more steps…
Subtract 12 from both sides of the equation.
k=72-12
Subtract 12 from 72.
k=60
k=60
Solve for k -(k+12)=6(-12)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top